Implementation Of Electronic Money In Developing Payment Transactions Through Islamic Economic Perspective - Abdul Majid Toyyibi (Universitas Islam Negeri (UIN) Walisongo Semarang, 2019)
AbstractPurpose - By upholding the value of sharia principles economic activities. Electronic money is a financial transaction that is used by the community as a substitute for cash, and ottopay is part of it, to help become a financial intermediary with an electronic system through QR and billers.Method - The research is based on researching ottopay in its transactions by using a descriptive qualitative.Result - From the research method process used in the study resulted in the study that the implementation of ottopay in topping up by filling directly via the bank ATM or through an agent by clicking the wallet menu then top up and following the steps until the confirmation is successful and the balance is ready whenever it can be used.Implication - The existence of the Ottopay system is a support for the community to be able to think forward in the world of finance and technology, in addition, ottopay can be used as a business opportunity to provide benefits in the form of added value in the form of turnover that can be owned by merchants and can be used as additional income for the community. Originality - The implementation of ottopay between users and publishers and users and merchants is in accordance with the rules of the DSN MUI fatwa, therefore the benefits of the ottopay application can guarantee security, easy and practical use so that people's economic turnaround is faster because it has an electronic digital system.